Effectiveness of IT training in primary schools. - Tan, Bee Tin. (2008)
As society enters the age of information technology (IT), schools play an important role to prepare its students to meet the needs of the future. Teachers need to be trained to implement IT in education. The purpose of this study was to assess the effectiveness of IT training provided by the Ministry of Education, Singapore, to equip teachers with pedagogical skills to integrate IT into the curriculum.